2019
DOI: 10.2147/copd.s207855
|View full text |Cite
|
Sign up to set email alerts
|

<p>Circulating syndecan-1 as a novel biomarker relates to lung function, systemic inflammation, and exacerbation in COPD</p>

Abstract: IntroductionPatients with COPD often show increased systemic inflammation which is associated with lower functional status, greater exacerbation risk, and worse clinical outcomes. Syndecans (SDCs), a family of transmembrane heparan sulfate proteoglycans (HSPGs), have been found to involve in inflammatory processes in many chronic inflammatory diseases. The aim of this preliminary clinical study was to investigate the possible association between two SDCs, SDC-1 and SDC-4, with lung function, systemic inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 26 publications
0
13
1
Order By: Relevance
“…25 TM, a 557-amino-acid type I transmembrane protein on the endothelium, binds exosite I on thrombin to alter thrombin specificity toward protein C. 29 The thrombin-TM complex activates protein C and thrombin-activatable fibrinolysis inhibitor, 30 thus inhibiting thrombus formation 31 and complement activation. 32 Under certain pathologic conditions, such as acute inflammation, 33,34 hyperglycemia, 35,36 endotoxemia, 37 ischemia-reperfusion injury, 33,38 and bypass surgery, 39,40 or stimulation with tumor necrosis factor a 41,42 and atrial natriuretic peptide, 43 the ectodomains of Sdc-1 and TM are cleaved by leukocyte-derived proteases, metalloproteinases, and heparinase. Therefore, increased plasma levels of Sdc-1 have been observed in patients with inflammation, 40 sepsis, 44 traumatic brain injury, 38 hemorrhagic shock, 45 disseminated intravascular coagulation (DIC), 46 and respiratory failure.…”
Section: Introductionmentioning
confidence: 99%
“…25 TM, a 557-amino-acid type I transmembrane protein on the endothelium, binds exosite I on thrombin to alter thrombin specificity toward protein C. 29 The thrombin-TM complex activates protein C and thrombin-activatable fibrinolysis inhibitor, 30 thus inhibiting thrombus formation 31 and complement activation. 32 Under certain pathologic conditions, such as acute inflammation, 33,34 hyperglycemia, 35,36 endotoxemia, 37 ischemia-reperfusion injury, 33,38 and bypass surgery, 39,40 or stimulation with tumor necrosis factor a 41,42 and atrial natriuretic peptide, 43 the ectodomains of Sdc-1 and TM are cleaved by leukocyte-derived proteases, metalloproteinases, and heparinase. Therefore, increased plasma levels of Sdc-1 have been observed in patients with inflammation, 40 sepsis, 44 traumatic brain injury, 38 hemorrhagic shock, 45 disseminated intravascular coagulation (DIC), 46 and respiratory failure.…”
Section: Introductionmentioning
confidence: 99%
“…32 Given that the shedding of soluble SDC extracellular domain can be detected in peripheral blood, SDC may be used as a biomarker for the diagnosis and prognosis of some diseases. 33 It has been found that soluble SDC1 can be used for noninvasive diagnosis in patients with chronic toxic hepatitis, 34 and it is effective in predicting the prognosis of patients with multiple myeloma, cervical cancer and other malignant tumors. [35][36][37] However, little is known about SDC4 shedding.…”
Section: Discussionmentioning
confidence: 99%
“…AECOPD is related to poor health outcomes, increased morbidity, and mortality rates [ 82 , 83 ]. The diagnostic and therapeutic management of AECOPD is still considered insufficient due to its heterogeneity and complexity [ 84 ].…”
Section: Copd Exacerbation-related Biomarkersmentioning
confidence: 99%